Czech Writers on the Trauma of Exile - Korda-Petrović, Aleksandra (Migrations in the Slavic Cultural Space. From the Middle Ages to the Present Day, 2022)
At various points in history, Czech writers were forced to live in exile or chose to emigrate voluntarily. Using a few selected examples, the paper analyses the personal perspective on exile reflected through the phenomenon of nostalgia (as in the example of Czech authors until the 20th century), the quest for personal and creative freedom (as in the example of Czech dissident writers) and the modern perspective on migrations and migrants (as in the example of a modern novel). The paper represents an attempt to distinguish between different forms of trauma driving the urge to leave one’s homeland and face another, different culture. Special attention is paid to the questions of bilingualism, biliteracy and binationalism, which become a key for the interpretation of the works of the selected Czech authors. The theoretical starting point is found in the works of Ivan Dorovski, Helena Koskova and Aleksandar Ilić.